1997
DOI: 10.1093/toxsci/36.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Toxicity of a Mixture of Nine Chemicals in Rats: Detecting Interactive Effects with a Fractionated Two-Level Factorial Design

Abstract: . (1997). Fundam. AppL Toxicol. 36,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The present study was intended (1) to find out whether simultaneous administration of nine chemicals at a concentration equal to the "no-observed-adverse-effect level" (NOAEL) for each of them would result in a NOAEL for the combination and (2) to test the usefulness of fractionated factorial models to detect possible interactions between chemicals in the mixture. A 4-week oral/ inhalatory study in male Wistar rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Full factorial designs (see, for example, 28 ) provide good data on interaction eects among chemicals, but are limited by practical constraint to a few chemicals (c) and dose levels (m) because the number of required dose groups is then large (m c ). Fractionated factorial designs for laboratory studies reduce this restriction 29 , but these can also be resource intensive. Thus, it is important to develop methods that oer ecient experimental designs for the laboratory that will also produce easily interpretable results.…”
Section: Introductionmentioning
confidence: 99%
“…Full factorial designs (see, for example, 28 ) provide good data on interaction eects among chemicals, but are limited by practical constraint to a few chemicals (c) and dose levels (m) because the number of required dose groups is then large (m c ). Fractionated factorial designs for laboratory studies reduce this restriction 29 , but these can also be resource intensive. Thus, it is important to develop methods that oer ecient experimental designs for the laboratory that will also produce easily interpretable results.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we use Groten et al (1991, 1996) to demonstrate how nonregular designs can be more cost efficient than regular designs. Our second study is taken from Groten et al (1996, 1997) and we show that nonregular designs can provide additional information on the estimates of some effects that regular designs are unable to do.…”
Section: Methodsmentioning
confidence: 75%
“…Exemplary applications and cost-efficiency comparisons of full factorial designs and regular fractional factorial designs in toxicity studies can be found in Nesnow et al (1995), Narotsky et al (1995), and Groten et al (1996,1997). We introduce nonregular fractional factorial designs and show their benefits using two studies reported in Groten et al (1996).…”
mentioning
confidence: 99%
“…Another approach in investigation of combined exposure toxicity is that of Groten et al, 17 who examined the subacute toxicity of a mixture from nine environmental chemicals at a concentration equal to the NOAEL or MOAEL of the single compounds in rats, using a fractionated two-level factorial design. They have found adverse effects not only in the MOAEL but also in some NOAEL groups.…”
Section: Discussionmentioning
confidence: 99%